2012
DOI: 10.9758/cpn.2012.10.1.54
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Personality Traits on Emotional Responses to Interpersonal Stress

Abstract: ObjectiveThe aim of the present study was to examine the impact of personality traits on emotional responses to interpersonal stress.MethodsThirty-two healthy college students (18 men, 14 women; age 25.2±2.7 years) participated in the study. Mood and anxiety were assessed with the Beck Depression Inventory and the State Trait Anxiety Inventory. Personality traits were assessed with the Interpersonal Sensitivity Measure (IPSM). The subjective emotional responses of participants to different (i.e., negative, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
(33 reference statements)
1
7
0
Order By: Relevance
“…The second aim of the present study was to evaluate the role of a personality trait, interpersonal sensitivity, among the association between bullying victimization and subtle paranoid thoughts and suspiciousness. Interestingly, IPSM total and subscale scores of the sample were similar to those reported by subjects who were at UHR of psychosis (Joo et al, ; Masillo et al, ), even though the sample presented mixed clinical characteristics. This result may be explained by the high rate of psychotic‐like experiences among adolescents (Kelleher et al, ).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The second aim of the present study was to evaluate the role of a personality trait, interpersonal sensitivity, among the association between bullying victimization and subtle paranoid thoughts and suspiciousness. Interestingly, IPSM total and subscale scores of the sample were similar to those reported by subjects who were at UHR of psychosis (Joo et al, ; Masillo et al, ), even though the sample presented mixed clinical characteristics. This result may be explained by the high rate of psychotic‐like experiences among adolescents (Kelleher et al, ).…”
Section: Discussionsupporting
confidence: 76%
“…psychosis (Joo et al, 2012;Masillo et al, 2012), even though the sample presented mixed clinical characteristics. This result may be explained by the high rate of psychotic-like experiences among adolescents (Kelleher et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, early studies indicated high interpersonal sensitivity and problems with self-confidence as being part of the subjective symptoms and observable behavioural changes occurring during the prodromal phase of schizophrenia (Subotnik & Nuechterlein, 1988;Häfner et al, 1992;Hambrecht et al, 1994). More recent studies have confirmed an association between interpersonal sensitivity, avoidant coping strategies, persecutory ideations and depressive symptoms in the ultra-high-risk and non-clinical samples (Valmaggia et al, 2007;Green et al, 2011;Masillo et al, 2012;Joo et al, 2012). These findings suggest that individuals who have problems in interpersonal sensitivity tend to modify their behaviour to comply with others' expectation in an attempt to minimize the risk of criticism or rejections.…”
Section: Introductionmentioning
confidence: 91%
“…This is consistent with the result of Watkins, 23 but not consistent with that of Nolen-Hoeksema et al 27 Another study showed that some characteristics including the severity of depression were not different between genders. 28,29 So the coping and ruminative style by gender needs further research.…”
Section: Discussionmentioning
confidence: 99%